Suwałki city experiences from the First and Second World War . - Łach, Halina (City and War, 2021)
Before the First and Second World Wars, Suwałki was situated in the extreme northern border area. Due to their geographic location, they experienced the dramatic effects of both wars. Before the outbreak of World War I, it was the capital of the Suwałki’s Governorate in the northern part of the Kingdom of Poland under Russian rule. The area of the Governorate was delimited in the west by the Russian-Prussian border. After the end of the war and Poland’s independence regaining, Suwałki became part of the Second Polish Republic. They became the seat of the Suwałki’s District Office of the lying within the Białystok voivodeship in the north of the country. The district bordered on German East Prussia in the west, and with Lithuania in the north and east. The city located near the Prussian border was of great military importance. In the event of a war with the German Empire, the Suwałki’s Governorate was treated by the Russians as a protection zone from the western side and as a foreground for the concentration of troops and an attack deep into East Prussia. In the Second Polish Republic, the Suwałki Region was a buffer zone between Lithuania and German East Prussia. It also created the conditions for planning a flanking attack on one or the other enemy. Both world wars left their mark on the everyday life of the city and its inhabitants. After the Russians were forced out, Suwałki and the Suwałki Region found themselves under German occupation. The occupiers exploited the area and population economically until the end of the war. However, during the Second World War, the Suwałki Region was incorporated into the German Reich and from the first days the Germans started to exterminate the population physically.